«A violent and harmful measure»: quarantines in Peru and the emergence of a Pan-American health policy (1850 - 1905) - Palma, Patricia (2021)
This article analyzes the imposition of quarantines in Peru and the debates that emerged around their implementation as a public health policy. The time frame ranges from the yellow fever epidemic in the 1850s to the 1905 Washington Sanitary Conference, which unified maritime public health criteria in the Americas. The study argues that discussions about the economic and social costs of imposing quarantines have been a constant in the history of public health in Peru and Latin America. The limited effectiveness of these policies led authorities to rethink their imposition and to implement alternative measures to prevent the spread of epidemics.